FAKTOR – FAKTOR SISWA MEMILIH SEKOLAH DI SEKOLAH MENENGAH ATAS NEGERI 2 PERANAP KABUPATEN INDRAGIRI HULU - Yuliani, Elva; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Baturijal Hulu Village, Peranap Sub-district of Indragiri Hulu Regency, whose research objects are first graders (1), two (2) and three (3) who attend school at Secondary School 2 Peranap. This study aims to see and know what factors internal and external factors of students continuing education in Secondary School Second Rice. This study looks at the theory of rational action. The population of this study are children who are sitting in first grade (1), two (2), and three (3) Senior Secondary School 2 Rice, Sampling using Probability Sampling. Then the data is analyzed by using descriptive quantitative method. Based on the result of the analysis found that students choose school in Secondary School 2 Roles consisting of internal and external factors are dominant on external factors based on family factors, school environment and their playmate compared with internal based on their own desires, ideals and talents. Keywords: Internal Factors, External Factors, Rational Actions, School Choices